KANO Model: A study to identify important attributes for customer satisfaction in a shoe store - Pereira, Gustavo Alves; Souza, Wiliam Santos; de Jesus, Willyans Santos; Muniz, Emerson Cleister Lima; de Souza, João Artur (Revista Gestão da Produção Operações e Sistemas, 2022)
Purpose – To identify which requirements are most important for generating customer satisfaction in a footwear company, through the application of the KANO Model. Design/methodology/approach – A questionnaire was applied by non-probabilistic sampling to collect information, created based on the literature on the subject under study. To ensure its reliability, Cronbach's α was applied as a parameter. For analysis and categorization of requirements, the research followed the guidelines of the Kano Model. Findings – The requirements are framed in mandatory, one-dimensional and attractive attributes. Of these, the mandatory attributes, essential to guarantee customer satisfaction, have already been prioritized by management. It was also found that the strategies used by the company meet about 88% of the identified requirements. Originality/value – The prior identification of the main customer requirements in the company's sector, its detailed analysis and categorization into attributes is the key value of the research, bringing direct benefits to management and its customers. The results allowed management to visualize analytically which of its actions directly contribute to customer satisfaction. And which demanded a joint effort from the company, but without adding much value to customer satisfaction. This, in turn, directly contributes to a better strategic alignment of the company's actions, which now prioritize the delivery and improvement of products/services that benefit all stakeholders. Keywords - KANO model. Customer satisfaction. Shoes store. Service improvement.